#TITLE_ALTERNATIVE# - SETYO ARDIANTO (NIM : 12208007); Pembimbing : Ir. Leksono Mucharam, M.Sc. ,Ph.D., ERWAN
Liquid loading is a common problem that occured and become a serious problem in gas wells. This phenomena is the effect of fluid accumulation in bottom hole of well leading pressure drawdown of well lower so it can decline rate of production gas. Due to rate of production gas declining, gas canÃ‚Â’t carry droplets of fluid flowing to surface so that gas well productivity will decline and accumulation of fluids in bottom hole cause the well die. Deliquification is methods to overcome liquid loading problems in gas wells. There are several methods of deliquification that have been developed in petroleum industry, one of them is using small tube. This methode can be an effective method to overcome liquid loading. The purpose of this method is to lift fluids out from tubing with particular velocity. By using pipe with smaller diameter, liquid from bottom hole is easier to uplift due to slug that formed in pipe. Laboratory studies conducted to analyze two-phase flow that occurs in small tube. Experiment was done using N2 gas as the gas phase and water as the liquid phase. The pressure that use in experiment is between 2 psi to 8 psi. From unloading sequence in experiment, flow pattern that occured in pipe is slug flow. Slug flow is the most effective flow to uplift liquids from bottom hole to surface. Analysis of two-phase flow is also performed the calculation of pressure gradients using two methods to compare the results measured in laboratory with mathematical calculations and to determine an appropriate correlation for experimental design.